INDONESIAN POLITICAL PUNDITS IN THE EYES OF THE MEDIA - Silvanus Alvin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Political pundits are one of the elements present in political communication, especially in countries that adhere to a democratic system. This research seeks to answer two big questions, who are and what criteria can make individuals referred to as pundits by the media? So, what is the role of pundits so that the media must quote their statements and make them news sources? This qualitative research uses a case study scheme with an in-depth interview data collection process to answer the research questions. Five informants from different media became the research sources. From this research, it was found that pundits must have certain educational qualification standards. However, that standard alone is not enough as they must also have a close relationship with journalists in order to be interviewed as pundits. another interesting finding is that the role of pundits in the media is similar as those who provide explanations of political situations. However, each media also has additional roles depending on the direction of each media. This is also discussed in this research.